Adjuvant sunitinib in patients with high-risk renal cell carcinoma: safety, therapy management, and patient-reported outcomes in the S-TRAC trial. (23rd August 2018) - Staehler, M; Motzer, R J; George, D J; Pandha, H S; Donskov, F; Escudier, B; Pantuck, A J; Patel, A; DeAnnuntis, L; Bhattacharyya, H; Ramaswamy, K; Zanotti, G; et al.
Abstract: Background: Adjuvant sunitinib has significantly improved disease-free survival versus placebo in patients with renal cell carcinoma at high risk of recurrence post-nephrectomy (hazard ratio 0.76; 95% confidence interval, 0.59–0.98; two-sided P  =   0.03). We report safety, therapy management, and patient-reported outcomes for patients receiving sunitinib and placebo in the S-TRAC trial. Patients and methods: Patients were stratified by the University of California, Los Angeles Integrated Staging System and Eastern Cooperative Oncology Group performance status score, and randomized (1 : 1) to receive sunitinib (50 mg/day) or placebo. Single dose reductions to 37.5 mg, dose delays, and dose interruptions were used to manage adverse events (AEs). Patients' health-related quality of life, including key symptoms typically associated with sunitinib, were evaluated with the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30). Results: Patients maintained treatment for 9.5 (mean, SD 4.4) and 10.3 (mean, SD 3.7) months in the sunitinib and placebo arms, respectively. In the sunitinib arm, key AEs occurred ∼1 month (median) after start of treatment and resolved within ∼3.5 weeks (median). Many (40.6%) AEs leading to permanent discontinuation were grade 1/2, and most (87.2%) resolved or were resolving by 28 days after last treatment. Patients taking sunitinib showed a significantly lower EORTC QLQ-C30 overall health status score versus placebo, although this reduction was not clinically meaningful. Patients reported symptoms typically related to sunitinib treatment with diarrhea and loss of appetite showing clinically meaningful increases. Conclusions: In S-TRAC, AEs were predictable, manageable, and reversible via dose interruptions, dose reductions, and/or standard supportive medical therapy. Patients on sunitinib did report increased symptoms and reduced HRQoL, but these changes were generally not clinically meaningful, apart from appetite loss and diarrhea, and were expected in the context of known sunitinib effects. Clinical trial registration: ClinicalTrials.gov, NCT00375674.